From Science to Action: Exploring the Potential of Artificial Intelligence to Strengthen Climate and Agricultural Research Capacities in Africa - Smith Ruiz, Paulina; Grossi, Amanda; Chipunza, Unity (2025)
Artificial Intelligence (AI) offers new opportunities to improve the efficiency, accessibility, and inclusiveness of e-learning in agricultural and climate research. This InfoNote examines how AI tools can accelerate content development and strengthen capacity-building initiatives across Africa, drawing on the experience of the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) as a case example. Using the AICCRA-supported course Integrating Gender in Cost-Benefit Analysis of Climate Interventions as a test case, several AI tools—NOLEJ, Khanmigo, and Google’s Learn Your Way—were assessed across four criteria: quality and innovation, accessibility and inclusion, and resource optimization.